Medan Identitas Seniman Kontemporer - Muh. Faisal (Emik, 2019)
Ideological differentiation in the field of art in the city of Makassar is about the search for identity in contemporary culture. In this region, there are many turbulent art discourses that try to present art identities in line with changes at the cultural level. One of its ideological domains is the discourse of modern art and the postmodern art discourse that is displayed through the process of creation and presentation patterns of art. The ideological knowledge of artists is closely related to the knowledge and symbolic abilities that they create through art. Upheaval between artists was also shown through economic conditions that influenced the orientation of the creation of works of art. While the identity of artists is classified based on 1). Individual art identity as a characteristic from birth or formed based on life history, 2). Group art identity in recognition of group ideas, and 3). National art identity as a binding cultural identity. Furthermore, the characteristics of contemporary art in Makassar are marked by the development of industries and art institutions that are presented based on the process of disseminating values ​​(diffusion). In responding to changes in contemporary art; hence there is repetition and differentiation in presenting cultural-industrial-based artistic identities. These concepts are practiced based on the differentiation of artists in presenting discourse on contemporary art in Makassar as part of an aesthetic regime. Art upheaval is also displayed through art presentation events (exhibitions) which can not be separated from the discourse system, ideological ideas, and visual experiences between artists. In the presentation of art (exhibition), industrial power also influences how the artwork is treated and discourse in accordance with cultural events faced by humans; as displayed at the Makassar Biennale exhibition in 2015 and in 2017. At the biennial vulnerability, repitition and differentiation of art can be read and evaluated. That the extent of representation of the artwork is culturally constructed. Keywords: Artist identity, repetition, differentiation, and contemporary art.